Debt Reduction and Economic Activity : Occa Paper No.68. (Occasional Papers; Occasional Paper ;, 1990)
This paper focuses on principles and various aspects of debt reduction and economic activity. The paper analyzes the effect of debt and debt-service reduction on the contractual and market values of a country's debt and also describes the IMF staff's preliminary attempts to describe and quantify the macroeconomic effects of debt and debt-service reduction. The method by which the buyback is financed is critical in determining how much debt reduction takes place, or, alternatively put, how much the price of debt rises. It is assumed in this paper that individual creditors are free to retain their existing claims and that these cannot be subordinated to new claims. It should be recognized at the outset that the approach used is but one of several possibilities. It should also be emphasized that the discussion is preliminary and that results will need to be reassessed as less restrictive assumptions are employed and as our understanding of the important economic relationships involved improves.